Software interactivo y aprendizaje de circuitos eléctricos en tercero de bachillerato de la Unidad Educativa Santa Mariana de Jesús - Secaira Cuji, Melani Lisbeth (2023)
The difficulties presented by students in learning physics, especially in understanding basic electrical circuits, and the lack of physical laboratories, have prompted teachers to use technological tools provided by ICTs to solve these problems. For this reason, this research aims to determine the incidence of using the CIRCUIT SIMULATOR APPLET software in learning electrical circuits in third-year high school students of "The Santa Mariana de Jesús" Educational Unit during 2021-2022. It is an online software, free and easy to use. It was a research with a quantitative approach at a descriptive level with a pre-experimental research design. It was applied to 35 third-year baccalaureate students of parallel "C." Two instruments were used for data collection: an observation sheet and an objective test (pretest and posttest). With the results obtained through the Wilcoxon non-parametric test, it was determined that the use of the software positively affects learning through the design and simulation of electrical circuits, helping to strengthen theoretical and practical knowledge, as well as arousing the interest of students to learn, motivating them to participate actively during class. Therefore, interactive software is recommended as a technological resource to improve teaching-learning and as an option for experimentation spaces (virtual laboratories).